Appraisal of Existing Frameworks on Judicial Independence in Nigeria - Ishmael U. Gwunireama (Activa Yuris: Jurnal Hukum, 2022)
Frameworks enhance the independence of the judiciary. Thus, there are different types of frameworks on the independence of the judiciary: legal and institutional. These are subjected to examination to bring them in line with current realities. This has necessitated the volume of pieces of literature proposing frameworks for reforms. Thus, in addition to the legal and institutional frameworks is the textual framework. The legal frameworks cover legislative enactments like the Constitution of the Federal Republic of Nigeria 1999(as amended), institutional frameworks like the regulations handed down by the National Judicial Council (NJC) and textual frameworks which are academic works of scholars, jurists and legal practitioners. This paper undertook an appraisal these frameworks and made proposals, like an amendment to s. 271 CFRN 1999, for further reforms, towards enhancing judicial impendence in Nigeria and aligning it with international standards.